miR-31-5p Regulates Type I Interferon by Targeting SLC15A4 in Plasmacytoid Dendritic Cells of Systemic Lupus Erythematosus - Li S; Wu Q; Jiang Z; Wu Y; Li Y; Ni B; Xiao J; Zhai Z (Dove Medical Press, 2022)
Shifei Li,1 Qijun Wu,1 Zhuyan Jiang,1 Yaguang Wu,1 Yuhong Li,2 Bing Ni,3 Jun Xiao,4 Zhifang Zhai1 1Department of Dermatology, Southwest Hospital of Third Military Medical University, Chongqing, People's Republic of China; 2Department of Cell Biology, Third Military Medical University, Chongqing, People's Republic of China; 3Department of Pathophysiology, Third Military Medical University, Chongqing, People's Republic of China; 4Department of Cardiovascular Medicine, Chongqing University Central Hospital, Chongqing, People's Republic of ChinaCorrespondence: Jun Xiao, Department of Cardiovascular Medicine, Chongqing University Central Hospital, Chongqing, People's Republic of China, Email xj73wy@163.com Zhifang Zhai, Department of Dermatology, Southwest Hospital of Third Military Medical University, Chongqing, People's Republic of China, Email zhaizf1004@163.comBackground: Plasmacytoid dendritic cells (pDCs) are the main producers of type I interferon (IFN-I), and the excessive production of IFN-I is a hallmark of systemic lupus erythematosus (SLE). Both SLC15A4 and miR-31-5p are SLE susceptibility-related genes, and SLC15A4 has been implicated an important role in endolysosomal toll-like receptor (TLR) activation in pDCs. However, whether miR-31-5p exerts a regulating effect on SLC15A4 expression in pDCs is unclear.Methods: The expression of SLC15A4 and miR-31-5p in peripheral blood mononuclear cells (PBMCs) of SLE patients was measured by RT-qPCR analyses. The quantitative analysis of IFN-α secretion in the patients' serum was performed by ELISA assay. Luciferase-reporter assay was applied to confirm the interaction between miR-31-5p and SLC15A4. The expression of miR-31-5p, SLC15A4 and IFN-stimulated genes (ISGs, such as MX1, OAS1 and IFIT3) was detected by Western blot and RT-qPCR assays and further IRF5 phosphorylation was evaluated by immunofluorescence after transfected with miR-31-5p mimics or inhibitor in THP-1 and CAL-1 cells.Results: The expression of miR-31-5p was downregulated and negatively correlated with the overexpression of SLC15A4 in PBMCs of SLE patients. In addition to this, the secretion of IFN-α was overexpressed in sera of SLE and positively correlated with SLC15A4 level. We found that miR-31-5p directly targeted SLC15A4 and negatively regulated the expression of SLC15A4 in THP-1 and CAL-1 cells. In vitro inhibition of miR-31-5p increased the phosphorylation of IRF5 and the induction of ISGs stimulated by R848, overexpression of miR-31-5p get the reverse results.Conclusion: miR-31-5p might involve in SLE pathogenesis through regulating IFN-I expression by negatively regulating SLC15A4 to increase the levels of IFN-α and ISGs in pDCs.Keywords: systemic lupus erythematosus, miR-31-5p, SLC15A4, type I interferon, plasmacytoid dendritic cell, inflammation